Demand response potential of aggregated high-temperature storage radiators. (November 2019) - Cai, Hanmin; You, Shi; Klyapovskiy, Sergey; Bindner, Henrik W.
Abstract: This study experimentally evaluates the demand response potential of aggregated high-temperature storage radiators to support intermittent solar photovoltaic (PV) production. Nine storage radiators on one floor of an office building located in Copenhagen's Nordhavn area are aggregated. Their demand response potential to compensate for the forecast errors of production from a large-scale PV installation in the same area is analysed. From experimental results, it is found out that the aggregated storage radiators have an activation time of 15 seconds and could provide a significant amount of energy storage while maintaining end-users' comfort.